What Are the Barriers to Human Papillomavirus Vaccination for Male in South Korea? - Sangrak Bae; Sooyoun Kim (Urogenital Tract Infection)
The human papillomavirus (HPV) virus causes genital warts, a sexually transmitted disease, as well as cervical and vulvar cancer in females and penile cancer in males. In addition, it this virus causes various diseases, including head and neck cancer and anal cancer. Vaccines can prevent malignant tumors caused by the HPV virus, and various projects are being conducted to eradicate HPV worldwide. The national inoculation program is a representative project among them. In Korea, only females are vaccinated; males are not included in the national mandatory vaccination list. Various reasons preventing HPV vaccination for males include cost-effectiveness, fear and misperception of side effects after vaccination, problems with the effectiveness of vaccination, and lack of social awareness about the need for vaccination, including parents, and the lack of research on male HPV disease. As female’s right to health is emphasized, HPV disease, which has become more important in treatment, will never be cured if it is managed only for females. Because the disease is transmitted sexually, managing and controlling HPV in males is also essential. In that sense, males must also be included as nationally required vaccination targets.